How does consumers' skepticism affect advertising claims? - Tien, Cheryl (School of Marketing, Curtin Business School, 2010)
This research provides some empirical findings of the relationships between the antecedents as well as the outcomes variables of consumers? skepticism toward advertising. Consumer skepticism toward advertising is defined as the tendency toward disbelief of advertising claims (Obermiller and Spangenberg, 1998). The beauty product industry is used as a context of study, due to the proliferation of manipulative ad claims in the industry. For the purpose of a preliminary study, this paper will employ one product category and a fictitious brand to examine consumers? skepticism toward advertising. The fictitious brand choice and product category choice has been derived from a focus group study. Analysis has revealed that self-esteem, consumers? susceptibility to interpersonal influences to informational factors and marketplace knowledge does not have a significant relationship with consumers? skepticism toward advertising as hypothesized. However, cynicism and consumer susceptibility of interpersonal influences to normative factors are found to be strong predictors of consumers? skepticism toward advertising. Consumers? skepticism toward advertising is also found to influence inferences of manipulative intent positively; this finding empirically supports the gap in Campbell?s (1995) study on inferences of manipulative intent. Inferences of manipulative intent also have significant relationships with attitude toward the advertisement and product judgment. The implications and recommendations are also discussed.